Modelo de un sistema contable basado en costos ABC para las Empresas dedicadas a las actividades de faenamiento, caso PROCARBA - Aldáz Mejía, Andrea de los Angeles (2007)
Different businesses in this case, slaughtering companies, require a financial information system - reliable and timely economic allowed establish the necessary tools to be competitive and maintain your product market at a low cost. This information system as well as presenting information states financial analysis should allow different costs incurred in the company and how resources have been used to obtain the final product. for this Procarba reason requires an accounting system to show the cost of each of the products offered to the market. This can be achieved by applying system cost by activity because it distributes the costs of resources in fairly among all products.